Selling and Buying Bodong Motor Perspective of Law No. 8 of 1999 Concerning Consumer Protection and Islamic Law (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2023)
Consumer protection in consumer protection laws are all efforts thatguarantee legal certainty to provide protection to consumers. Legal certainty in thiscase is that consumers have the right to obtain all information from goods soldboth in terms of specifications and quality.In practice, there are still buying andselling transactions that are not in accordance with legal certainty. As in the villageof Plangkapan, there are still buying and selling fake motorbikes that are notaccompanied by official papers or documents. Here the object is not clear whetherthe motorbike was stolen or the papers were lost. The people who bought themotorbike did not see whether the motorbike was stolen or the documents werelost, but only saw its useful days for the benefit of its activities.This type of research is field research, with a socio-juridicalapproach and using observation methods, documentation interviews usingpurposive sampling techniques which are then analyzed using descriptive-qualitative methods. The problem is how to buy and sell bogus motorbikes inPlangkapan Village, Tambak District, Banyumas Regency and how to buy and sellfake motorbikes in Plangkapan Village from the Perspective of Law No. 8 of 1999concerning Consumer Protection and Islamic Law.The results showed that in the practice of buying and selling motorbikesin the practice of buying and selling in the village of Plangkapan, the resultsshowed that the motorbike was stolen, removed from the dealer and bought a usedmotorbike, then the motorbike was sold without official papers or documents. Thebuyer did not get clear information about the motorbike. But the buyer still agreedwith the buying and selling system because motorcycle buyers only see in terms of benefits. In Islamic law buying and selling motorbikes from theft is a fasid law.However, if buying and selling fake motorbikes is not the result of theft, it ispermissible. Whereas in the Consumer Protection Act, the sale and purchase ofbodong motorbikes violates the provisions on consumer rights, the obligations ofbusiness actors and actions that are prohibited by business actors, as well as thelack of ownership protection for consumers